Vitreous Substitutes - Shorya Vardhan Azad; Deepankur Mahajan; Sidharth Sain; Amit Jain; Brijesh Takkar; Rajvardhan Azad (Delhi Journal of Ophthalmology)
Vitreous humour is a gelatinous structure that not only maintains the intra ocular pressure but also plays an important role in nourishment of the eye. The search for an ideal vitreous substitute that is transparent, elastic and biocompatible like the vitreous itself is still on. Over a period of time, various compounds have been used such as balanced salt solution, air, gases, perflourocarbons liquids and silicone oil. This review article looks at various conventional and investigational vitreous substitutes in detail.